Diagnosis and treatment of early renal disease in patients with type 2 diabetes mellitus: what are the clinical needs? - Mann, Johannes; Rossing, Peter; Wiecek, Andrzej; Rosivall, Laszlo; Mark, Patrick; Mayer, Gert (Nephrology Dialysis Transplantation, 2015)
Renal disease is prevalent in patients with diabetes mellitus type 2. Aggressive metabolic control and lowering of systemic and/or intraglomerular blood pressure are effective interventions but not without side effects. Thus a better, early identification of patients at risk for incidence or progression to end-stage renal failure by the use of new, validated biomarkers is highly desirable. In the majority of patients, hypertension and hyperglycaemia are pathogenetically important pathways for the progression of renal disease. Nonetheless even aggressive therapy targeting these factors does not eliminate the risk of end-stage renal failure and experimental evidence suggests that many other pathways (e.g. tubulointerstitial hypoxia or inflammation etc.) also contribute. As their individual importance might vary from patient to patient, interventions which interfere are likely not to be therapeutically effective in all subjects. In this situation, an option to preserve the statistical power of clinical trials is to rely on biomarkers that reflect individual pathophysiology. In current clinical practice, albuminuria is the biomarker that has been best evaluated to guide stratified/personalized therapy but there is a clear need to expand our diagnostic abilities.
EVALuna2:3877